Key Macrophage Responses to Infection With Mycobacterium tuberculosis Are Co-Regulated by microRNAs and DNA Methylation - Looney, Monika; Lorenc, Rachel; Halushka, Marc K.; Karakousis, Petros C. (Frontiers in Immunology, 2021)
Tuberculosis (TB) is the leading cause of death from infection with a single bacterial pathogen. Host macrophages are the primary cell type infected with Mycobacterium tuberculosis (Mtb), the organism that causes TB. Macrophage response pathways are regulated by various factors, including microRNAs (miRNAs) and epigenetic changes that can shape the outcome of infection. Although dysregulation of both miRNAs and DNA methylation have been studied in the context of Mtb infection, studies have not yet investigated how these two processes may jointly co-regulate critical anti-TB pathways in primary human macrophages. In the current study, we integrated genome-wide analyses of miRNA abundance and DNA methylation status with mRNA transcriptomics in Mtb-infected primary human macrophages to decipher which macrophage functions may be subject to control by these two types of regulation. Using in vitro macrophage infection models and next generation sequencing, we found that miRNAs and methylation changes work to co-regulate important macrophage response processes, including immune cell activation, macrophage metabolism, and AMPK pathway signaling.